Peer Education and Sexual Risk Behavior Among Adolescents: Does Urban Status Matter? - Sumaryani, Sri; Ningrum, Sri Andini Widya; Prihatiningsih, Titi Savitri; Haryanti, Fitri; Gunadi, Agus (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: As a result of elevated sexual risk behaviors among teenagers, millions of adolescents face sexual and reproductive health challenges, including high rates of an unfulfilled need for contraceptives, unintended pregnancy, and unsafe abortion. To develop their skills and prevent adolescent sexual activity from being unsafe, especially in urban areas, teachers and peers were advised that teaching adolescents about reproductive health should be carried out at any school. AIM: This study aims to evaluate the effect of peer education on the prevention of adolescent activity at sexual risk in urban areas. METHODS: This research was a pre-experimental quantitative approach with a one-group pre-post-test model. The survey used in this study had 63 respondents. Samples were collected using a purposeful sampling process. The research was conducted in April at SMP Negeri X Yogyakarta until June 2017. In this analysis, the independent variable was peer education, while the dependent variable was the prevention of sexual risk activity among adolescents. RESULTS: The Wilcoxon sign-rank test data analysis showed that there were no significant differences in the prevention of sexual risk behavior among adolescents in urban areas at pre- and post-sexual education through p-value peer education = 0.086. CONCLUSION: There is no significant impact on reducing adolescent sexual risk behaviors in urban areas through peer education. The media may significantly influence the prevention of the conduct of urban adolescents at sexual risk. To prevent sexual risk behavior among adolescents in an urban environment, further research is recommended to find the best intervention using more profound internal and external relevant variables and media impact association study.